Pengaruh Evaluasi Diri Terhadap Kepercayaan Diri Dalam Pergaulan di Masa Pembelajaran Daring - Faizin, Nur Auliya Rahmah; Noorrizki, Rakhmaditya Dewi (Universitas Negeri Malang, 2022)
Abstract: In 2020, the COVID-19 virus was declared to have entered Indonesia. The World Health Organization has designated COVID-19 as a pandemic. President Joko Widodo decided to impose large-scale social restrictions (PSBB), activities in schools and workplaces were closed and activities in public places or facilities and religious places were also restricted. Online learning as an alternative to learning is immediately implemented so that students continue to get an education and can still interact with friends and teachers even though they are quarantining at home during a pandemic. Online learning which initially became a new experience for students then began to bring up one by one obstacles, one of which was the lack of interaction by students with the social environment. The purpose of this study was to identify the factors causing the lack of social interaction of students with their social environment and determine whether self-evaluation can affect self-confidence and can be a solution to increase self-confidence. The method used in this article is literature review. It was found that the lack of social interaction caused by lack of intense communication with peers, lack of social support, and self-evaluation was influential in increasing self-confidence. Keywords: self-confidence; self-evaluation; online learning; social interaction Abstrak: Pada tahun 2020, virus COVID-19 dinyatakan telah masuk ke Indonesia. World Health Organization telah menetapkan status COVID-19 sebagai pandemi. Presiden Joko Widodo memutuskan untuk memberlakukan Pembatasan Sosial Berskala Besar (PSBB), kegiatan di sekolah dan tempat kerja diliburkan lalu kegiatan di tempat atau fasilitas umum dan tempat keagamaan juga dibatasi. Pembelajaran daring sebagai alternatif pembelajaran segera dilaksanakan agar para pelajar tetap mendapatkan pendidikan dan tetap dapat berinteraksi dengan teman dan juga para guru meskipun sedang melakukan karantina di rumah disaat pandemi. Pembelajaran daring yang awalnya menjadi pengalaman baru bagi para pelajar kemudian mulai memunculkan satu persatu hambatan, salah satunya kurangnya interaksi oleh para siswa dengan lingkungan sosial. Tujuan penelitian ini adalah untuk mengidentifikasi faktor penyebab kurangnya interaksi sosial siswa dengan lingkungan sosialnya dan mengetahui apakah evaluasi diri dapat mempengaruhi kepercayaan diri serta dapat menjadi solusi untuk meningkatkan kepercayaan diri. Metode yang digunakan dalam artikel ini adalah literature review. Ditemukan hasil bahwa kurangnya interaksi sosial disebabkan oleh kurangnya komunikasi yang intens dengan teman sebaya, kurangnya dukungan sosial, serta evaluasi diri berpengaruh dalam meningkatkan kepercayaan diri. Kata kunci: kepercayaan diri; evaluasi diri; pembelajaran daring; interaksi sosial